2018
DOI: 10.11648/j.ajtab.20180401.13
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Citizenship Behaviour and Employees’ Performance Assessment: The Case of Dire Dawa University

Abstract: Although a vast amount of researches have been done on the relations of Organizational Citizenship Behavior (OCB) and employees' performance in western or foreign context, there is a little or no empirical evidence in domestic context. However, scholars argue that geographical and cultural differences can bring about differences in OCB. Thus, this empirical study was conducted to find out the relationship between employees' performance and OCB in Ethiopian context, particularly in Dire Dawa. The study was also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The questionnaire was self-administered through face-to-face sessions, over a period of six months. The respondents were asked to score on a Likert scale of 1 to 5 (where 1: strongly disagree to 5: strongly agree), their level of agreement with the various issues under consideration like that outlined in other studies (Dinka, 2018; Basu et al , 2017; Skarlicki and Latham, 2009). Out of the 100 questionnaires distributed, 88 were retrieved; however, upon further checks, only 86 were valid and were used for the analysis, representing a high response rate of 86 percent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire was self-administered through face-to-face sessions, over a period of six months. The respondents were asked to score on a Likert scale of 1 to 5 (where 1: strongly disagree to 5: strongly agree), their level of agreement with the various issues under consideration like that outlined in other studies (Dinka, 2018; Basu et al , 2017; Skarlicki and Latham, 2009). Out of the 100 questionnaires distributed, 88 were retrieved; however, upon further checks, only 86 were valid and were used for the analysis, representing a high response rate of 86 percent.…”
Section: Methodsmentioning
confidence: 99%
“…They further indicated that OCB factors such as sportsmanship and civic virtue are vital predictors of employee retention in an organization. In addition, according to Dinka (2018), OCB can affect organizational performance, and further increase group performance because it helps people to work together. Over the past 15 years, research on the relationship between OCB and employee performance, has emerged as a primary focus and many researchers have proven a positive relationship between OCBs and employee performance, thus making clear the interdependence of OCB on employee performance and vice versa (Sun et al, 2007;Ehrhart et al, 2006;DeGroot and Brownlee, 2006;Koys, 2001;Allen and Rush, 1998):…”
Section: Development Of Hypothesismentioning
confidence: 99%
“…Organizational citizenship behaviour describes a person's voluntary commitment within an organization that is not part of his or her contractual tasks. For example, helping others with heavy workloads, does not take extra breaks, and keep up with developments in the company (Dinka, 2018;Park, 2016). Organizational citizenship behaviour is indeterminate and is not officially linked to incentive and performance appraisal systems in organizations (Klotz et al, 2018).…”
Section: Organizational Citizenship Behaviourmentioning
confidence: 99%
“…According to Hemaloshinee and Nomahaza (2017), organizational citizenship behavior donates to decreasing the organization's need to provide resources, cohesion, and administrative unity and helping employees for exertion by allotting space to effectual scheduling as well as resolving the issues, dilemmas, and problems. Dinka (2018) and Pekaar (2016) explained that A person's voluntary willingness to the organization for OCB is not for contractual tasks. Helping others in workloads does not keep burden, and keep up betterment in the company.…”
Section: Introductionmentioning
confidence: 99%